Do espetáculo ao ensino: chuva de bala no país de Mossoró na perspectiva da história local - Oliveira, Ocimara Fernandes Negreiros (2021)
The city of Mossoró (RN) was marked as the first city in the Northeast to expel the band of cangaceiro Lampião, with the participation of local groups. This episode is portrayed annually in a theatrical presentation adapted from the text of poet and writer Tarcísio Gurgel. Problematizing the use of this show for teaching, the research aims to analyze the show Chuva de Bala in the Country of Mossoró as a strategy for teaching Local History in the elementary education in Mossoró. In order to reach the proposed objective, we started with an investigation of a qualitative approach, based on a bibliographical research. For the purposes of didactic organization, this research was carried out in three main pillars. In the first, we analyze the configurations of the teaching of Local History in Brazil and in Mossoró/RN through the debate of eight works and three Pedagogical Political Projects (PPP) of schools in this municipality. We call on the studies of Romanowski and Ens (2006) to elaborate the state of the art; Bittencourt (2008), Neves (2015) and Silva (2013) in the debate on Local History; the National Curriculum Parameters (PCN) of 1997 and the Common National Curriculum Base (BNCC) of 2018 to verify the regulations regarding the theme; and, finally, Japiassu (1994) and Fazenda (1994) to address the need for a more interdisciplinary curriculum. The second pillar was about the invention of the show rain of bullet in the Country of Mossoró in the light of Local History, based on the original play and the text of the 2018 show. We therefore resorted to Hobsbawn (1997) to work on the invention of traditions ; Bezerra (2014), Falcão (2013) and Gurgel (2015) on the told narrative; and Tamanini (2021) in image studies. In the third pillar, we diagnose the applicability of teaching local history in three municipal schools of Basic Education in Mossoró, through a questionnaire in virtual format applied to three teachers about their teaching practice. The results showed us that the approaches that the show rain of bullet in the country of Mossoró can take in the classroom do not exclusively serve the issues of location, or even a relationship purely directed to space-time, but they can to contribute to learning in an interdisciplinary way, privileging social relationships and, above all, the feeling of belonging, citizenship and, finally, the construction of individual and collective identity